Synergistic Effect of Rhizobium Inoculation with Co-inoculants on Growth and Yield of Lentil (Lens culinaris Medikus) - Biswas, P. K.; Bhowmick, M. K.; Malik, G. C.; Banerjee, Mahua; Malik, G. C.; Mitra, S. R. (International Journal of Bio-resource and Stress Management, 2023)
A three-year field study was conducted during rabi seasons of 2005-06, 2006-07 and 2007-08 at the Pulses and Oilseeds Research Sub-station, Beldanga, Murshidabad, West Bengal, India to study the effect of seed inoculation with Rhizobium (LLR 22) alone and in combination with PGPR (CRB 1, CRB 2, RB 1, RB 2, PUR 34 and KB 133) on growth, nodulation and seed yield of lentil. The results revealed that significantly higher seed yield was obtained when Rhizobium is inoculated with PGPR strain (KB 133) as compared to uninoculated control. Yield advantages due to inoculation with Rhizobium+PGPR strain KB 133, Rhizobium+PGPR strain PUR 34, Rhizobium+PGPR strain RB 1 and Rhizobium+PGPR strain CRB 1 were 50.65, 29.41, 28.81 and 26.80%, respectively, over uninoculated control and 30.30, 11.93, 11.41 and 11.06%, respectively, over Rhizobium inoculation only